Informing the NHS Outcomes Framework: evaluating meaningful health outcomes for children with neurodisability using multiple methods including systematic review, qualitative research, Delphi survey and consensus meeting - Christopher Morris; Astrid Janssens; Amanda Allard; Joanne Thompson Coon; Valerie Shilling; Richard Tomlinson; Jane Williams; Andrew Fellowes; Morwenna Rogers; Karen Allen; Bryony Beresford; Colin Green; et al. (Health Services and Delivery Research, 2014)
Background: The identification of suitable outcome measures will improve the evaluation of integrated NHS care for the large number of children affected by neurodisability, and has the potential to encourage the provision of more appropriate and effective health care. This research sought to appraise the potential of patient-reported outcome measures (PROMs) for children and young people with neurodisability. Aim: This research aimed (i) to identify key outcomes of health care for children with neurodisability, beyond morbidity and mortality, from the perspectives of children, parents and professionals; (ii) to critically appraise existing generic multidimensional PROMs; and (iii) to examine whether or not the key outcomes might be measured by existing PROMs. We also sought agreement on a definition of neurodisability. Methods: Data were gathered in three main ways, (i) a systematic review identified eligible generic multidimensional PROMs and peer-reviewed studies evaluating psychometric performance using English-language questionnaires. Studies were appraised for methodological quality and psychometric performance was appraised using standard criteria. (ii) Focus groups and interviews with children and young people with neurodisability, and separately with parents, sought to identify important outcomes of NHS care, and their feedback on example PROM questionnaires. (iii) An online Delphi survey was conducted with a multidisciplinary sample of health professionals to seek agreement on appropriate NHS outcomes. In addition, we convened a consensus meeting with a small nominal group of young people, parents and professionals; the group sought agreement on a core set of important health outcomes. Results: From the systematic review, we identified 126 papers that reported eligible evidence regarding the psychometric performance of 25 PROMs. Evidence of psychometric robustness was more favourable for a small number of PROMs: KIDSCREEN (generic), DISABKIDS (chronic-generic) and Child Health Utility 9D (preference-based measure). The Pediatric Quality of Life Inventory and KINDL offer both self-report and a proxy report version for a range of age bands, but evidence of their psychometric performance was weaker. Evidence was lacking in one or more respects for all candidate PROMs, in both general populations and those with neurodisability. Proxy reporting was found generally to be poorly correlated with self-report. Focus groups and interviews included 54 children and young people, and 53 parents. The more important health outcomes were felt to be communication, emotional well-being, pain, mobility, independence/self-care, worry/mental health, social activities and sleep. In addition, parents of children with intellectual impairment identified behaviour, toileting and safety as important outcomes. Participants suggested problems with the face validity of example PROM questionnaires for measuring NHS care. In the Delphi survey, 276 clinicians from a wide range of professions contributed to at least one of four rounds. Professionals rated pain, hearing, seeing, sleep, toileting, mobility and communication as key goals for the NHS but also identified treating neurological symptoms as important. Professionals in the Delphi survey and parents working with the research team agreed a proposed definition for neurodisability. The consensus meeting confirmed overlap between the outcomes identified as important by young people, parents and professionals, but not complete agreement. Conclusions: There was agreement between young people, parents and professionals regarding a core suite of more important health outcomes: communication, emotional well-being, pain, mobility, independence/self-care, worry/mental health, social activities and sleep. In addition, behaviour, toileting and safety were identified as important by parents. This research suggests that it would be appropriate to measure these constructs using PROMs to assess health care. None of the candidate PROMs in the review adequately captures all of the identified constructs, and there is inadequate evidence that candidate PROMs are psychometrically robust for use across children with neurodisability. Further consultation with young people, families and professionals is warranted to support the use of PROMs to measure NHS outcomes. Research to test potential PROMs with different age groups and conditions would be valuable. Funding: The National Institute for Health Research Health Services and Delivery Research programme.